Managing risks and opportunities in multilingual knowledge economies: the possibilities of ethnical investment movement to sustaining biolinguistic diversity - Michael Singh; Christopher Scanlon (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2003)
This paper argues that the ethical investment view of business, which acknowledges the interdependent relationships between financial, social and environmental risks, can be justifiably extended to include the sustainability of linguistic diversity. The first section of this paper briefly summarises the current state of the world's languages, noting that the vast majority of the world's languages are at risk of extinction. The reasons for declining linguistic diversity are explored in some detail. This is followed by a consideration of the intimate connections between language, knowledge and environmental sustainability. The next section explores the increasing significance of the multilingual knowledge economies including the emergence of linguistic niche markets, diasporic market segments and the cosmopolitan marketplace (Singh, 2001 b). Given the interrelationships between language, knowledge, ecological sustainability and the limits of economic over-development, the final section explores the potential for the ethical investment view of business, which acknowledges these interrelationships, to be explicitly extended to sustaining multicultural and linguistic diversity.